Methodical instructions for the calculation and graphic work on electrical engineering "Calculation of parameters and characteristics of electrotechnical devices" - Boliukh, Volodymyr F.; Markov, V. S.; Honcharov, Yevgen Viktorovych; Poliakov, I. V.; Kriukova, Nataliya Valeriivna (Національний технічний університет "Харківський політехнічний інститут", 2024)
This publication is dedicated to calculation and graphic work from the discipline "Electrical engineering" on the topic "Calculation of parameters and characteristics of electrotechnical devices". The purpose of the work is to consolidate theoretical knowledge and practice practical skills in calculating such electrotechnical devices as: single-phase transformers, shunt- and series-wound DC motors, three-phase induction motors. Here, four control problems are formulated, input data options for them are presented, and examples of calculations of typical problems are given. The specific scope of work is specified by the lecturer who conducts a course of lectures on the specified discipline. Input data variants for specific Problems are presented in Tables 1 -4, and the headings of these Tables are provided on page 24. It is enough to copy this page and enter the specific input data of your option and, using these Tables, perform the necessary calculations. The report on calculation and graphic work must be neat, executed in accordance with the established form. It begins with a title page, a sample of which is shown in Fig. 1. When drawing up the report, it is necessary to indicate the complete statement of the Problems and the relevant input data according to the variant, accompanying schematic diagrams, the order of calculations and its results and graphs. Schematic diagrams are drawn with the help of tools according to state standards. Graphs of dependencies should be made with standard letter designations of values and units of measurement indicated on the axes.
Keywords: methodical instructions; calculation; graphic work; electrical engineering; electrotechnical devices; calculation of parameters